A prospective study of the radiological changes in the cervical spine in early rheumatoid disease. Issue 2 (April 1981) - Winfield, J; Cooke, D; Brook, A S; Corbett, M
Abstract : The cervical spine radiographs of 100 patients with early rheumatoid disease were studied annually, on a prospective basis, for a mean follow-up period of 7 years 2 months. Atlantoaxial subluxation developed in 12 patients. The subluxation was more frequent in females, more severe in patients with progressive, seropositive, erosive rheumatoid disease, and more marked in patients treated with oral corticosteroids. Subaxial subluxation, affecting upper cervical disc levels, occurred in a further 20 patients. Three patients developed vertical subluxation. The mobility of the cervical spine affects the degree of subluxation achieved, and when assessing serial films for subluxation it may be necessary to measure the cervical spine flexion before deciding whether subluxation has progressed or not. Over 80% of the patients with subluxation developed the first evidence of subluxation within 2 years of disease onset. Subluxation in the cervical spine is not, therefore, a late complication of rheumatoid disease. During the follow-up period none of the patients developed neurological signs.